Naẓarīyya al-Nabawi ‘Inda al-Fārābīy - Amal Fathullah Zarkasyi (Al-Jami'ah Research Centre, 1999)
After the spread of Islam in a wide area, and the concept of monotheism had been known by most people, another teaching emerged. The teaching was against the principles of monotheism. The teaching that emerged in the second century of Hijra, called for polytheism and was influenced by Hinduistic teaching especially that of reincarnation. One of its teaching was refusal of revelation and prophecy. Since then, the debate on this issue emerged between its supporters and its opponents. At this condition al-Farabi came and try to combine between religion and philosophy. Al-Farabi's concept on prophecy was much influenced by Aristoteles concept of dream. Even though, Al-Farabi raised a different thought from that of Aristoteles. According to Aristoteles, dream cannot be part of revelation While al-Farabi saw that human being with his or her imagination could relate to the